Peran Zikir dalam Menentramkan Hati; Kajian Tarekat Khalwatiyah Syekh Yusuf di Tombolo - Puspa Melati, Mahdia; Damis, Rahmi; Nurbaethy, Andy (Sulesana: Jurnal Wawasan Keislaman, 2025)
The essential problem of this study concerns the understanding of the followers of the Khalwatiyah Syekh Yusuf order regarding the role of dhikr (remembrance of God) in attaining inner tranquility. This main problem is further elaborated into two sub-questions: 1) What is the meaning of dhikr according to the Khalwatiyah Syekh Yusuf order? 2) What are the implications of dhikr for achieving inner peace?This study employs a qualitative-descriptive approach within the framework of field research. The sampling technique applied is snowball sampling. Data collection methods include observation, interviews, and documentation. The procedures for data processing and analysis consist of three stages: data collection, data reduction, data presentation, and conclusion drawing. The findings reveal that the meaning of dhikr in the Khalwatiyah Syekh Yusuf order is the remembrance of Allah (God) deeply embedded within the heart. Thus, dhikr is not merely verbal utterance but is manifested in every activity, state, or condition in which the individual remains consciously aware of and connected to Allah. The implications of dhikr for inner tranquility are reflected in its effect upon the soul and heart through the regular practice of remembrance, which fosters serenity and peace. However, this effect is contingent upon the individual’s full awareness of Allah. From such awareness arises a sense of happiness that influences not only the heart but also the physical body.